Future Directions in the Diagnosis and Treatment of APDS and IEI: a Survey of German IEI Centers - Vanselow, Sven; Hanitsch, Leif; Hauck, Fabian; Körholz, Julia; Maccari, Maria-Elena; Meinhardt, Andrea; Sogkas, Georgios; Schuetz, Catharina; Grimbacher, Bodo (Frontiers in Immunology, 2023)
The diagnosis and treatment of inborn errors of immunity (IEI) is a major challenge as the individual conditions are rare and often characterized by a variety of symptoms, which are often non diseasespecific. Ideally, patients are treated in dedicated centers by physicians who specialize in the management of primary immune disorders. In this study, we used the example of Activated PI3Kδ syndrome (APDS), a rare IEI with an estimated prevalence of 1:1,000,000. We conducted surveys by questionnaire and interviewed physicians at different IEI centers in Germany. We queried structural aspects of IEI care in Germany, diagnostic procedures in IEI care (including molecular diagnostics), distribution of APDS patients, APDS symptoms and severity, treatment algorithms in APDS, the role of stem cell transplantation and targeted therapies in IEI with focus on APDS. We were especially interested in how genetic diagnostics may influence treatment decisions, e.g. with regard to targeted therapies. Most centers care for both pediatric and adult patients. A total of 28 APDS patients are currently being treated at the centers we surveyed. Patient journeys vary considerably, as does severity of disease. Genetic diagnosis continues to gain importance -whole genome sequencing is likely to become routine in IEI in the next few years. According to the experts interviewed, stem cell transplantation and -with new molecules being approved -targeted therapies, will gain in importance for the treatment of APDS and IEI in general.